Encyclopedia of Inorganic and Bioinorganic Chemistry 2021
DOI: 10.1002/9781119951438.eibc0244.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Zintl Compounds

Abstract: The term “Zintl phase” refers to a class of compounds and is used to recognize contributions to the field of solid‐state inorganic chemistry by Eduard Zintl. Zintl phases were initially defined as a subgroup of intermetallic phases, where the anions or anionic network could be considered formally to be valence satisfied. In the historical description, these compounds are formed from electropositive elements from groups 1, 2 that, in a formal sense, donate their electrons to the electronegative elements from gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 231 publications
0
11
0
Order By: Relevance
“…Zintl phases are electronically classified as intermetallic phases, assuming that an electron transfer from the less electronegative to the more electronegative elements takes place [10,11] . Hence, most of them are described as valence compounds and exhibit ionic as well as covalent bonding [12,13] . Concerning the combination of alkali metals and group 14 and 15 elements, a variety of isolated clusters can be found, [14,15] which can be described using the (8‐ N ) rule [16–18] .…”
Section: Introductionmentioning
confidence: 99%
“…Zintl phases are electronically classified as intermetallic phases, assuming that an electron transfer from the less electronegative to the more electronegative elements takes place [10,11] . Hence, most of them are described as valence compounds and exhibit ionic as well as covalent bonding [12,13] . Concerning the combination of alkali metals and group 14 and 15 elements, a variety of isolated clusters can be found, [14,15] which can be described using the (8‐ N ) rule [16–18] .…”
Section: Introductionmentioning
confidence: 99%
“…Reacting, in the solid state, alkali metals and/or alkaline-earth metals with the metalloids (early p-block elements) generates a large number of compounds with unusual structures. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] In particular, one should notice that the structural diversity is greatly amplified if the realization of compounds containing more than one type of alkali metals and/or alkaline-earth metals are considered. [7][8][9][10][11][12][13][14] The different nature/ratios of elements in the chemical make-up of the compound leads to varied bonding arrangements, where the atoms of the metalloid use the electrons donated by the alkali metals or alkaline-earth metals and form 2D-or 3D-networks, chains and chain-like fragments, small clusters, dumbbells, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Reacting, in the solid state, alkali metals and/or alkaline‐earth metals with the metalloids (early p‐block elements) generates a large number of compounds with unusual structures [1–14] . In particular, one should notice that the structural diversity is greatly amplified if the realization of compounds containing more than one type of alkali metals and/or alkaline‐earth metals are considered [7–14] .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, tellurides are at the forefront of explorative efforts on charge density waves, , superconductors, , topological insulators, phase-change data storage materials, , and thermoelectrics. , To understand and, furthermore, predict the (physical) properties of a given material, it is also necessary to extract the relevant information from the (computed) electronic structure of the respective compound. , In the case of the tellurides, the electronic structures have often , been interpreted based on applications of the Zintl–Klemm-concept that has been originally introduced to relate the structural features of intermetallics of the main group elements to their electronic structures. In the framework of this formalism, the valence electrons are (formally) transferred from the more electropositive atom to the more electronegative atom(s) which constitute anions being isostructural to the modifications of isoelectronic elements. In the connection with the (formal) transfers of valence electrons, group-I-/-II-elements are also typically described as active metals due to their functions as active valence-electron donors in solids containing group-I- and/or group-II-elements; yet, more recent research showed that the applicableness of the aforementioned Zintl–Klemm formalism to tellurides is rather limited.…”
Section: Introductionmentioning
confidence: 99%